Experimentation on Greeting Before Entering the Classroom - Aisyah Fadilah; Sovani Rizky Handayani; Sulis Putri Hidayat; Imam Tabroni; Scherschligt Osca; Woolnough Cale (Yayasan Adra Karima Hubbi, 2023)
Background. Character is a pattern of thought and a pattern of one's actions that are carried out directly. According to Thomas Lickona, character education contains three main elements, namely knowing goodness, loving goodness, and doing goodness, meaning that character refers to a series of knowledge, attitudes, motivation, and behavior. Therefore, this character needs to be considered, especially for students Purpose. A student must have good character in his life from waking up to sleeping again. In this research, we will help develop good character for students, with the aim that it can be applied in their home environment. Method. This research is collaborative by involving students as resource persons and objects of action. Results. , This action is carried out as a form of field practice. Conclusion. From the results of our research it can be concluded that this research can be declared successful and can be applied by schools, but researchers cannot guarantee whether it can last long or not. Hopefully, habituation at school can be developed and practiced in the outside environment such as when at home, in the market, at the playground, and others